Struktur Dramatik Lakon “Mintaraga” Sajian Wayang Wong Sriwedari - Wisnu Samodro; Sarwanto Sarwanto (LP2M ISBI Bandung, 2019)
AbstractThis research examines the dramatic structure of the Wayang wong Sriwedari performance in the Mintaraga story. Mintaraga story is composed of Serat Arjuna Wiwaha by Empu Kanwa and is the third part of Mahabharata Book. The Mintaraga is one of the most interesting plays to study in its dramatic structure. This research is qualitative with descriptive analysis. The concepts used in the analysis processes are the classification of characters by Sutopo, Freytag’s Pyramid, and the plotting concept by Endaswara. The results show that the Mintaraga play uses protagonist characters, antagonist, tritagonist, and some supporting or additional characters that have a function to give a clearer picture related to the story to be conveyed. In addition, the performances of Wayang wong can be divided into five acts based on the Freytag Pyramid, which includes exposition, complication, climax, resolution, and conclusion.Keywords: dramatic structure, Mintaraga story, Freytag PyramidAbstrakPenelitian ini mengkaji struktur dramatik pementasan Wayang Wong Sriwedari Lakon “Mintaraga”. Lakon “Mintaraga” sendiri merupakan gubahan dari Serat Arjuna Wiwaha karya Empu Kanwa dan bagian ketiga dari Kitab Mahabarata. Lakon Mintaraga menjadi salah satu lakon yang menarik untuk dikaji struktur dramatiknya. Penelitian ini merupakan penelitian deskriptif kualitatif yang berupaya untuk menggambarkan atau menjelaskan suatu fenomena dengan menggunakan kata-kata. Analisis data menggunakan konsep klasifikasi tokoh dari Sutopo, Piramida Freytag, dan kaidah pengeplotan oleh Endaswara. Hasil penelitian menunjukkan bahwa pementasan lakon “Mintaraga” menggunakan tokoh-tokoh protagonis, antagonis, tritagonis dan beberapa tokoh pendukung atau tambahan yang memiliki fungsi untuk memberikan gambaran yang lebih jelas terkait dengan cerita yang ingin disampaikan. Selain itu, pementasan wayang wong tersebut dapat dibagi menjadi lima babak yang didasarkan pada Piramida Freytag, yang meliputi exposition, complication, climax, resolution, dan conclusion.Kata Kunci: struktur dramatik, lakon Mintaraga, Piramida Freytag